Предмет: Алгебра,
автор: МАНДАРИНЪ
Помогите пожалуйста ,срочно !
Приложения:
Ответы
Автор ответа:
0
а)(х2 - 2х - 5х +10)-(х2 - 4х +х - 4)=6
х2-2х-5х+10-х2+4х-х+4=6
-2х-5х+4х-х=6-4-10
-4х=-8| умножаем на -1, чтобы избавиться от минуса
4х=8
х=8:4
х=2
х2-2х-5х+10-х2+4х-х+4=6
-2х-5х+4х-х=6-4-10
-4х=-8| умножаем на -1, чтобы избавиться от минуса
4х=8
х=8:4
х=2
Похожие вопросы
Предмет: Математика,
автор: serepitkokatea
Предмет: Физика,
автор: dana88899911183
Предмет: Литература,
автор: Ihyuui
Предмет: Математика,
автор: Mokko2015
Предмет: История,
автор: маша107деловкина